Exploring Refusal Strategies among Female EFL Learners: Insights from Indonesian Islamic Boarding School - Zulfikar, Zulfikar (Universitas Negeri Medan, 2024)
This study investigated the types of refusal strategies employed by female English EFL learners at Daruzzahidin Islamic Boarding School. It utilized a qualitative approach, collecting data through a Discourse Completion Task and interviews with twenty and fifteen students, respectively. The results indicated that the most frequently used refusal strategy was indirect, followed by direct and adjunct strategies. The interviews revealed that the students' choice of refusal strategy was influenced by their family and school environments. This study supports previous research on refusal strategies, but contrasts with findings that suggest a different approach to refusal. The study highlights the importance of considering the social and cultural context in which language is used, as well as the individual differences in language expression. The findings also underscore the need for further research on refusal strategies, particularly using natural speech as data and exploring the topic across various fields such as psycholinguistics and sociolinguistics.